Rodzice o dobrej publicznej szkole dla swoich dzieci. Fenomenograficzna ilustracja - Alicja Jurgiel-Aleksander (Problemy Wczesnej Edukacji, 2021)
The purpose of this article is to try to empirically face the phenomenon of a good public school. However, not by following legislation demonstrating its public status, but by means of a simple question addressed to the parents of pupils in grades I to III as to how this phenomenon is understood by them. Based on a conversation with her parents, the author has made a phenomenographic reconstruction of the concepts behind the importance of a good public school. It turned out that, according to the parents, a good public school is identified with modern teaching methods (a), it is treated as an instrument for preserving the social status of the student (b), a tool for conveying the desired values (c), its meaning lies in shaping the disposition to learn. The author shows that in a cultural sense, the revealed categories of description show that it is difficult for us still to go beyond instrumental rationality in search of the meaning of a modern good public school and public good education.